Improving work-based learning in schools - Musset, Pauline (OECD Social, Employment and Migration Working Papers, 2019)
Looking at secondary schools, this paper analyses work-based learning (WBL) as an element of both general education and vocational programmes. The workplace is a powerful learning environment where technical skills can be learnt from expert practitioners using real-life equipment, while also acquiring key soft skills such as teamwork and communication. WBL offers students the opportunity to transition from school to work, while for employers it offers a means of recruitment. However, it can be challenging to engage employers. Quality requires good WBL design and supporting mechanisms. The length and sequencing of WBL are important. The equity risks of WBL also need to be managed. The paper considers different policy messages for schools and jurisdictions